UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BONGGOL BROKOLI (Brassica oleracea L. var. Italica) DENGAN METODE DPPH (1,1-Diphenyl-2-Picrylhydrazy) - Umaya, Chindy; Marbun, Nova Rianti; Br Sembiring, Tio Ranti Sari (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Broccoli (Brassica oleracea L. var. Italica) is a vegetable recognized for its abundant bioactive components, such as flavonoids, tannins, saponins, and vitamin C, which are linked to antioxidant capabilities. Notwithstanding its health advantages, the broccoli stalk is frequently disregarded and underexploited, despite its potential as a source of natural antioxidant chemicals. This work aims to assess the antioxidant activity of the ethanolic extract from broccoli stalks utilizing the DPPH method and to ascertain its IC₅₀ value. The extraction was conducted via the maceration method utilizing 70% ethanol, and the antioxidant activity was assessed through UV-Vis spectrophotometry at a peak wavelength of 516 nm. The results indicated that the ethanolic extract of broccoli stem possesses considerable antioxidant activity, with an IC₅₀ value of 35.74 µg/ml. The IC₅₀ value of vitamin C was shown to be 7.67 µg/ml. The results indicate that broccoli stalks may be a significant source of natural antioxidants. The validation of the analytical method demonstrated outstanding results, including linearity (r = 0.9989), accuracy (100.57%), and precision (%RSD = 0.5646%).